Oliver! - Moody, Ron; Wallis, Shani; Reed, Oliver; Reed, Carol (Columbia Pictures, 1968)
Musical adaptation of Charles Dickens's classic tale of an orphan who runs away from the orphanage and hooks up with a group of boys trained to be pickpockets by an elderly mentor. Oliver Twist is sold to a Dunstable undertaker after asking for more dinner at the orphanage. Escaping to London he is taken in by Fagin to join his gang of child pickpockets. Wrongly accused of a theft he meets a more kindly gentleman who takes him in, to the concern of one of Fagin's old pupils, the violent Bill Sykes. In the middle is Nancy, Sykes' girl whom Oliver has come to trust.